(untitled) (Eurasian Journal of Philology Science and Education, 2024)
The article reveals theoretical and practical aspects of the colour-symbol «white» in the poetic works of Bakhytzhan Kanapyanov in terms of semiotics. The use of colour symbolism in the works of B. Kanapyanov is individual due to a number of reasons associated with the depth of perception of the poet. Considering the artistic world of Kanapyanov, we actualize implicit meanings, reconstruct the course of the poet’s associative thoughts, connected to colourism. The aim of the study is to consider the signifier «white» in visual perception, to determine the interpretation of this signifier on the material of poetic works of B.M. Kanapyanov. In particular, the review of a number of theoretical works on semiotics and colour signification of «white». For the poet white colour means sanctity, virtue and purity that explains high frequency of its usage and, correspondingly, the reason of our addressing to the signifier «white» in the author’s poetic works. The article presents the semiotic analysis of the author’s poetic works by the interpretation of «white», it identifies perceptual and symbolic ways and means of creating the basic signs in the poetic texts. Each text prescribes the results of the analysis, defines semantic dominants through visual perception, reveales the symbolism of colour designation, which confirms the practical significance of the study. The value of the work lies in an attempt to reveal artistic world of B.M. Kanapyanov, the peculiarity of his perception of the world and creative processing of reality through the colours and the meanings they contain. Thus, on the example of the signifier «white» in visual perception, for each text the interpretation is defined and the symbolic meaning is revealed, which confirms, in particular, the importance of colour symbolism in the works of B.M. Kanapyanov and in a broader sense, the relevance of colour signification in modern science. Key words: colour-symbol, interpreter, designator, signifier, symbolic meaning, colour signification.